Respuesta :
complete the square
move the 3 aside and work in parenthasees
f(x)=(x^2+6x)+3
take 1/2 of 6 and square it (6/2=3, 3^2=9)
add 9 and -9 inside
f(x)=(x^2+6x+9-9)+3
factor perfect square
f(x)=((x+3)^2-9)+3
get rid of parenthases
f(x)=(x+3)^2-9+3
f(x)=(x+3)^2-6
2nd choice
move the 3 aside and work in parenthasees
f(x)=(x^2+6x)+3
take 1/2 of 6 and square it (6/2=3, 3^2=9)
add 9 and -9 inside
f(x)=(x^2+6x+9-9)+3
factor perfect square
f(x)=((x+3)^2-9)+3
get rid of parenthases
f(x)=(x+3)^2-9+3
f(x)=(x+3)^2-6
2nd choice